LEGAL PROTECTION OF CREDITORS AGAINST THE EXECUTION OF COLLATERAL OBJECTS IN THE EVENT OF THE DEBTOR'S BREACH OF PROMISE AT BANK MANDIRI KC SURABAYA GENTENGKALI - Reza Nugraha Putra; Waluyo (JARES (Journal of Academic Research and Sciences), 2023)
When the debtor neglects to make payments on his debt, an execution parate is made as a form of legal protection for creditors. The origin of the execution of mortgage rights can be traced back to this time. UUHT has provided a precise description of the execution that can be carried out in the event of a debtor's default, including holding an auction known as "execution parate". Empirical legal research does not only focus on the positive aspects of law but also its application or practice in the field. In addition, the methodology used in this research is qualitative. In addition, this study uses three types of legal materials, namely primary legal materials, secondary legal materials, and tertiary legal materials. This study shows that Article 6 UUHT contains requirements regarding legal protection for creditors. The form of a written agreement is another form of legal protection for creditors to be able to take back their rights from debtors with bad intentions to pay off their receivables, and banks can carry out parate executions if the debtor defaults.